Answer:
y = 6(x + 6)(x - 4).
Step-by-step explanation:
y = 6x^2 + 12x - 144
y = 6(x^2 + 2x - 24) Factoring the trinomial in the parentheses ,we get:
y = 6(x + 6)(x - 4)
Answer:
The answer is 1
Step-by-step explanation:
2(a+7)−7=9
Step 1: Simplify both sides of the equation.
2(a+7)−7=9
(2)(a)+(2)(7)+−7=9(Distribute)
2a+14+−7=9
(2a)+(14+−7)=9(Combine Like Terms)
2a+7=9
2a+7=9
Step 2: Subtract 7 from both sides.
2a+7−7=9−7
2a=2
Step 3: Divide both sides by 2.
2a
2
=
2
2
a=1
Answer:
angle U ( the third option down)
Step-by-step explanation:
The first question I think it’s A because 1.13 is larger than 1.2
I hope this helps